Failure mechanisms of reinforced thermoplastic pipe (RTP) with crack defects at longitudinal and circumferential orientations - Mustaffa, Z. (Elsevier Ltd, 2023)
Reinforced Thermoplastic Pipe (RTP) is a composite pipeline that has received considerable attention in the oil and gas applications due to benefits such as high strength and corrosion resistance. Limitations occurred, however, when the performance of this pipe-type towards various defects is still not fully addressed. Thus, this paper attempts to highlight the response of RTP imposed to crack failures using hydrostatic burst test and validated with numerical simulations under various internal pressures. Two defect orientations were studied, namely longitudinal and circumferential, as measured with respect to the pipeline length. The established Von-Mises stress criterion was used to compare the intact RTP performance, while Stress Intensity Factor (SIF) for the cracked RTP. Parametric studies having different crack dimensions were also investigated, with results showing that the longitudinal crack would be giving higher impact as compared to the circumferential one, even at low operating pressure. Observations on the RTP specimen's failure were also shared. Results obtained from this study would be beneficial in giving initial understandings to pipeline operators on the RTP behaviors towards crack failures. Â© 2023 Elsevier Ltd